KOMPARASI KEBIJAKAN PELAKSANAAN SUPERVISI PENDIDIKAN SEMESER GANJIL DAN SEMESTER GENAP DI SMAN 1 JUNJUNG SIRIH - Ratna Julia Putri; Dina Rahmadani; Felly Asra; Eviyarman Eviyarman; Darul Ilmi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze and compare the policies for implementing educational supervision during the odd and even semesters at SMAN 1 Junjung Sirih. Educational supervision is a strategic effort to enhance teachers’ professionalism and improve the quality of learning through continuous guidance, monitoring, and evaluation. This research employed a qualitative approach with a descriptive comparative method. The research participants consisted of the principal, vice principal for curriculum affairs, supervision team members, teachers, and educational staff selected through purposive sampling. The findings reveal significant differences in the focus of supervision policies between the odd and even semesters. During the odd semester, supervision primarily focuses on reviewing and guiding instructional administration, including teaching modules, semester programs, learning media, and assessment instruments. In contrast, supervision during the even semester emphasizes the evaluation of instructional practices, classroom observations, student learning outcomes, and feedback provision for teachers. Although several challenges were identified, such as the principal’s limited time, scheduling conflicts with school activities, and some teachers’ lack of confidence during classroom observations, the supervision process contributed positively to improving teachers’ professional competence and the overall quality of instruction. The novelty of this study lies in its comparative analysis of supervision policies across semesters, demonstrating that supervision strategies are adapted to the specific learning needs of each semester, thereby enhancing their effectiveness and sustainability.